Enhancing Care Quality and Wellness for Older Adults: Empathy Training in Nursing - Lusianah, Lusianah; Fajarini, Melati; Maharani, Cintya Narulita (Althea Medical Journal, 2025)
Background:  Empathy plays an essential role in older adult care and patient wellness, by strengthening healthcare quality and the nurse-patient relationship. This study evaluated the effectiveness of Carl Rogers-based empathy training in improving the capacity of empathy among nurses, particularly in caring for older adult patients and wellness. Methods: A quasi-experimental pre- and post-test design was conducted in October 2024 at Bekasi Regency Hospital, Indonesia. Nurses from inpatient and outpatient units were selected through purposive sampling. Empathy was assessed using the Interpersonal Reactivity Index (IRI) before and after a three-day training program. The analysis included overall empathy scores and four subdimensions: Empathic Concern (EC), Perspective Taking (PT), Fantasy Scale (FS), and Personal Distress (PD). Data were analyzed using the Wilcoxon signed-rank test and effect size calculations.Results: The mean total empathy score slightly decreased from 47.91±7.4 to 46.14±2.6 (p=0.190, r=0.22). However, significant improvements were observed in EC (p=0.004, r=0.51) and FS (p=0.007, r=0.42), whereas PD decreased significantly (p=0.001, r=0.61). No significant change was found in PT (p=0.457, r=0.12).  Conclusion: Short-term empathy training effectively enhances emotional dimensions of empathy, such as empathic concern and fantasy scale, while reducing personal distress. However, it does not significantly improve overall empathy scores. Long-term training, reinforcement strategies, and cognitive-based interventions may be needed to support sustained empathy developments in nursing care for older adults and patient wellness.